'Omics‐guided prediction of the pathway for metabolism of isoprene by Variovorax sp. WS11. (5th August 2022) - Dawson, Robin A.; Rix, Gregory D.; Crombie, Andrew T.; Murrell, J. Colin
Abstract: Bacteria that inhabit soils and the leaves of trees partially mitigate the release of the abundant volatile organic compound, isoprene (2‐methyl‐1, 3‐butadiene). While the initial steps of isoprene metabolism were identified in Rhodococcus sp. AD45 two decades ago, the isoprene metabolic pathway still remains largely undefined. Limited understanding of the functions of isoG, isoJ and aldH and uncertainty in the route of isoprene‐derived carbon into central metabolism have hindered our understanding of isoprene metabolism. These previously uncharacterised iso genes are essential in Variovorax sp. WS11, determined by targeted mutagenesis. Using combined 'omics‐based approaches, we propose the complete isoprene metabolic pathway. Isoprene is converted to propionyl‐CoA, which is assimilated by the chromosomally encoded methylmalonyl‐CoA pathway, requiring biotin and vitamin B12, with the plasmid‐encoded methylcitrate pathway potentially providing robustness against limitations in these vitamins. Key components of this pathway were induced by both isoprene and its initial oxidation product, epoxyisoprene, the principal inducer of isoprene metabolism in both Variovorax sp. WS11 and Rhodococcus sp. AD45. Analysis of the genomes of distinct isoprene‐degrading bacteria indicated that all of the genetic components of the methylcitrate and methylmalonyl‐CoA pathways are not always present in isoprene degraders, although incorporation of isoprene‐derived carbon via propionyl‐CoA and acetyl‐CoA is universally indicated.